2004
DOI: 10.1029/2003jd004484
|View full text |Cite
|
Sign up to set email alerts
|

New evidence for an ENSO impact on low‐latitude glaciers: Antizana 15, Andes of Ecuador, 0°28′S

Abstract: [1] Continuous monthly mass balance measurements from the ablation zone of Antizana 15 glacier in the Andes of Ecuador between January 1995 and December 2002 indicate a strong dependence on El Niño-Southern Oscillation (ENSO). Over the 8-year period investigated, mass balance was negative all year round during El Niño periods but remained close to equilibrium (positive anomalies) during La Niña events. On seasonal timescales, mean ablation rates remain at a quite constant level all year round, but interannual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
197
0
8

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(219 citation statements)
references
References 32 publications
14
197
0
8
Order By: Relevance
“…If this is correct, it implies that there is significant interannual variability in the ELA of the MGS and, thereby, also the Carstensz Glaciers. This seems reasonable given the significant variability in the monthly mass balance of the single intensely studied tropical glacier on the eastern side of the Pacific, Antizana in Ecuador (Francou et al 2004). In the Ecuadoran case, the monthly variability translated into 290 m of variation (4 sigma) in the annual ELA between 1994 and 2005 (Haeberli et al 2007).…”
Section: Glacier Mass Balance and Hypsometrymentioning
confidence: 81%
See 1 more Smart Citation
“…If this is correct, it implies that there is significant interannual variability in the ELA of the MGS and, thereby, also the Carstensz Glaciers. This seems reasonable given the significant variability in the monthly mass balance of the single intensely studied tropical glacier on the eastern side of the Pacific, Antizana in Ecuador (Francou et al 2004). In the Ecuadoran case, the monthly variability translated into 290 m of variation (4 sigma) in the annual ELA between 1994 and 2005 (Haeberli et al 2007).…”
Section: Glacier Mass Balance and Hypsometrymentioning
confidence: 81%
“…In the tropical Andes, Francou et al (2004) showed that the cumulative loss of ~25 m in water equivalent from Antizana Glacier in Ecuador over the eight-year period from 1995 to 2002 was due to the intensity of El Niño events in this interval. During El Niño events, glacier ablation increased because of atmospheric warming and decreased precipitation.…”
Section: Discussionmentioning
confidence: 99%
“…However, other factors that could contribute to a negative mass balance such as a decrease in solar radiation absorption due to less cloud cover should not be ruled out (Sicart et al 2003, Vuille et al 2003, Francou et al 2004, Gallaire et al 2010. Furthermore, in most studies, variation in the energy balance of tropical glaciers is dominated by net shortwave radiation, which is related to albedo, one of the variables controlling melting (Wagnon et al 1999a(Wagnon et al , 1999b.…”
Section: Introductionmentioning
confidence: 99%
“…For example, during a strong El Niño event, accelerated retreat of glaciers in Ecuador has been observed with a time lag of 3-6 months (Francou et al 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation